Diagnostico dos resíduos sólidos: um estudo de caso do município de São João de Pirabas-PA - LISBOA, Flavia Augusta Miranda (2019)
Among the major environmental problems of the last century there is the great production and disposal of solid waste improperly in the environment. This paper is a case study of the City of Sao. Joao Pirabas, which aims to diagnose and assess the situation of solid waste in the city and propose alternatives for integrated management. The data were collected on packaging, transport, regularity, frequency of collection and disposal of solid waste produced in the county, including health services that are the responsibility of the City. From the diagnosis was identified lack of integrated management of municipal solid waste, the inefficiency of the public collection, because it benefits only 67% of households in the city, noted another factor, besides the little importance given the issue of solid waste by the public administration, the availability of financial resources and a factor to be considered, mainly on the implementation and operation of a landfill, whereas the value for the issue and publishes municipal cleaning and only 5% of the Urban Land Tax, property tax, making it clear that with this amount of revenue and virtually impossible to build and maintain and operating a landfill. Regarding the Health Services was possible to verify the absence of the Plan of Waste Management of Health Services, PGSS, handling, storage and disposal systems, lack of training for civil servants who work directly in the management of such waste in these establishments. This study allowed to bring up proposals for the government to promote a managing these wastes efficiently.